Metamaterial-based passive radiative cooling technology - Yun, Weizhao (Nanyang Technological University, 2024)
Cooling technology is essential in life as energy consumption exists everywhere from household appliances to power station, which means large amount of heat will be produced during various procedures. At a time when the greenhouse effect is becoming more and more serious, releasing heat is of great importance to inhibit the global warming effect and keep temperature balance. Metamaterials are engineered materials with unique physical properties that are not found in natural occurring materials and have been widely applied in many fields. Recently, metamaterials are found to be promising in passive radiative cooling and become a hotpot in research. This paper aims to explore metamaterial-based passive radiative cooling technology and show how the optical properties can be manipulated by metamaterials to realize radiative cooling. A metamaterial-based radiator which is highly reflective at visible spectrum while totally transparent at mid-infrared frequencies will be constructed and simulated. By constructing metamaterials with specific structures, it is possible to realize different optical properties in a specific wavelength range and thus achieve the desired cooling performance.The FDTD software will be used in simulation to verify the availability to realize radiative cooling based on metamaterial structure.The effect of the materials parameters on the cooling performance will also be studied.